The Multidisciplinary Approach to The Study of Chronic Pelvic Pain (MAPP) Research Network*: Design and implementation of the Symptom Patterns Study (SPS). Issue 6 (23rd June 2020) - Clemens, J. Quentin; Kutch, Jason J.; Mayer, Emeran A.; Naliboff, Bruce D.; Rodriguez, Larissa V.; Klumpp, David J.; Schaeffer, Anthony J.; Kreder, Karl J.; Clauw, Daniel J.; Harte, Steven E.; Schrepf, Andrew D.; Williams, David A.; et al.
Abstract: Aims: The Multidisciplinary Approach to the Study of Chronic Pelvic Pain (MAPP) Research Network initiated a second observational cohort study—the Symptom Patterns Study (SPS)—to further investigate the underlying pathophysiology of Urologic Chronic Pelvic Pain Syndrome (UCPPS) and to discover factors associated with longitudinal symptom changes and responses to treatments. Methods: This multisite cohort study of males and females with UCPPS features a run‐in period of four weekly web‐based symptom assessments before a baseline visit, followed by quarterly assessments up to 36 months. Controls were also recruited and assessed at baseline and 6 months. Extensive clinical data assessing urological symptoms, nonurological pain, chronic overlapping pain syndromes, and psychosocial factors were collected. Diverse biospecimens for biomarker and microbiome studies, quantitative sensory testing (QST) data under multiple stimuli, and structural and functional neuroimaging scans were obtained under a standardized protocol. Results: Recruitment was initiated (July 2015) and completed (February 2019) at six discovery sites. A total of 620 males and females with UCPPS and 73 Controls were enrolled, including 83 UCPPS participants who re‐enrolled from the first MAPP Network cohort study (2009‐2012). Baseline neuroimaging scans, QST measures, and biospecimens were obtained on 578 UCPPS participants. The longitudinal follow‐up of the cohort is ongoing. Conclusions: This comprehensive characterization of a large UCPPS cohort with extended follow‐up greatly expands upon earlier MAPP Network studies and provides unprecedented opportunities to increase our understanding of UCPPS pathophysiology, factors associated with symptom change, clinically relevant patient phenotypes, and novel targets for future interventions.